What is the trend after Covid-19? A Political-Economic Analysis of the Pension Systems in Hong Kong and MACAU - Shanwen Guo; Liliang You; Qibin Wang (Faculty of Economic and Business, 2023)
The aging trend of the population in Hong Kong and Macau is evident, so the pension system is especially significant. This research paper uses document analysis and a double-case study as the research method. It uses path dependence and critical moments in historical institutionalism theory as the theoretical tools for political economy analysis. The discussion argues that “the social culture shaped by local politics,” “the combination of local economic development and economic structure,” and “influence from social structure” are the three main factors that influence the pension systems in Hong Kong and Macau, and are the fundamental reasons for the differences between the pension systems in Hong Kong and Macau. We also conclude that the outbreak of COVID-19 is causing the evolution of the pension systems in both regions to be converging.JEL Classification: H7, N9, O2, R5How to Cite:Guo, S., You, L., & Wang, Q. (2023). What is the Trend after Covid-19? A Political-Economic Analysis of the Pension Systems in Hongkong and Macau. Etikonomi, 22(1), 155–174. https://doi.org/10.15408/etk.v22i1.23737.